The Eratosthenes Coe in the Pollynet: First observations of the PollyXT-CYP at Limassol, Cyprus - Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Engelman, Ronny; Buhl, Johannes; Seifert, Patric; Baars, Holger; Yin, Zhenping; Hadjimitsis, Diofantos G.; Ansmann, Albert (My University, 2021)
A new generation PollyXT lidar system start on 27th of October 2020, continuous operation, at Limassol, Cyprus. The lidar system will become a key component within the EXCELSIOR H2020 EU Teaming project coordinated by the Cyprus University of Technology. The mission of the EXCELSIOR project is to upgrade the Remote Sensing & Geo-Environment Lab, established within the Faculty of Engineering & Technology of the Cyprus University of Technology, into a sustainable, viable and autonomous Centre of Excellence, called the ERATOSTHENES Center of Excellence (ECoE). The PollyXT-CYP will be hosted by the ERATOSTHENES CoE for its permanent operation aiming to link the Centre to ACTRIS and PollyNet. Its task will be to document the complex mixture of the different aerosol species and clouds over the Eastern Mediterranean. The system is continuously running and since the first observations in …